2015
DOI: 10.1038/srep16686
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Sleep Duration and Overweight/Obesity: Results from 66,817 Chinese Adolescents

Abstract: The findings about the shapes of associations between sleep duration and overweight/obesity in adolescents were largely inconsistent in the existing literature. We examined the functional forms of the associations between sleep duration and overweight/obesity in 66,817 Chinese adolescents by modelling sleep duration categorically and continuously. The adjusted ORs (95% CI) of overweight (with 7.0–8.9 h of sleep being considered the reference group) for subjects reporting <5.0 hours, 5.0–6.9 hours and ≥9.0 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 44 publications
2
53
1
4
Order By: Relevance
“…Conversely, another systematic review including both cross-sectional and prospective studies of adolescents found that the relationship between decreased sleep duration and weight status is inconsistent, and concluded that it remains inconclusive as to whether or not decreased sleep duration affects weight status significantly (Guidolin and Gradisar, 2012). A study of Chinese adolescents in 2015 reported that there was also substantial heterogeneity across studies concerning the shape of the associations between sleep duration and overweight/obesity with being shown the Ushaped associations in adolescents, and these discrepancies in results between studies might be driven by study locations, study design, different age of the sample, varied exposure categories and different confounders adjusted (Wu et al, 2015). A more recent review revealed that sleep characteristics are associated most strongly with obesity from cardiovascular risk factors, and more positive associations were observed in studies including adolescents (Matthews and Pantesco, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another systematic review including both cross-sectional and prospective studies of adolescents found that the relationship between decreased sleep duration and weight status is inconsistent, and concluded that it remains inconclusive as to whether or not decreased sleep duration affects weight status significantly (Guidolin and Gradisar, 2012). A study of Chinese adolescents in 2015 reported that there was also substantial heterogeneity across studies concerning the shape of the associations between sleep duration and overweight/obesity with being shown the Ushaped associations in adolescents, and these discrepancies in results between studies might be driven by study locations, study design, different age of the sample, varied exposure categories and different confounders adjusted (Wu et al, 2015). A more recent review revealed that sleep characteristics are associated most strongly with obesity from cardiovascular risk factors, and more positive associations were observed in studies including adolescents (Matthews and Pantesco, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…13 The additional and important new insight from the present study is that prolonged sleep duration was also associated with overweight and obesity. The association between prolonged sleep duration and overweight/obesity was examined in adolescents and adults in previous studies, 21,22 while it was seldom assessed in preschool-aged children.…”
Section: Discussionmentioning
confidence: 99%
“…Además, se debe considerar los resultados reportados el año 2015, en un estudio realizado a 66.817 adolescentes chinos que reveló asociaciones positivas entre sobrepeso y obesidad y horas de sueño 18 . Una debilidad del estudio, es que al ser este de corte transversal, se dificulta la determinación de causalidad.…”
Section: Bajounclassified